2014
DOI: 10.1016/j.cirp.2014.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Flow visualization and characterization for optimized MQL machining of composites

Abstract: Limited information is available on the effect of Minimum Quantity Lubrication (MQL) parameters (oil flow rate OFR, air flow rate AFR, nozzle orientation and distance from the cutting zone) on flow characteristics. 'Particle Image Velocimetry' and 'Phase Doppler Anemometry' flow visualization methods were used to define the optimal MQL jet for better penetration and cooling/lubrication; coherent, small magnitude/number of vorticities, and small droplets of high velocity. Effect of flow characteristics on cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Therefore, minimum quantity lubrication (MQL) provides a viable alternative, in addition to the economic and environmental benefits. The optimization of MQL parameters in milling of CFRP was recently studied through flow visualization to determine the optimal MQL parameters for improved cooling and lubrication capacity [94]. It was found that better machining performance and dimensional accuracy were obtained with a coherent jet with small magnitude/number of vorticities, and small droplets of high velocity.…”
Section: Dry Machining and Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…Therefore, minimum quantity lubrication (MQL) provides a viable alternative, in addition to the economic and environmental benefits. The optimization of MQL parameters in milling of CFRP was recently studied through flow visualization to determine the optimal MQL parameters for improved cooling and lubrication capacity [94]. It was found that better machining performance and dimensional accuracy were obtained with a coherent jet with small magnitude/number of vorticities, and small droplets of high velocity.…”
Section: Dry Machining and Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…They found that the airflow field will play a drag role on the entry of micro droplets at a high jet velocity when micro droplets are injected along the 'entry flow' in the airflow field (avoiding the 'return flow'). Iskandar et al [12] found that the jet velocity researches at 35 m/s when air flow rate is set as 31 L/min. Therefore, although dosage of NEBL is lower than traditional MWFs, the 'useful' flow rate is higher thanks to bigger jet speed of NEBL droplets with the help of high pressure gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, 27% improvement of surface roughness is possible during end milling of mild steel under 900ml/h flow rate of MQL while uncoated end mill cutter of HSS used, and it is also evident that MQL works efficiently at less speed and depth of cut [71]. Iskandar et al, [72] conducted experiments to establish optimum MQL conditions by considering various parameters such as flow rate of oil and air, spray angle, nozzle distance, and flow characteristics of the milling process of carbon fiber reinforced plastics (CFRP). The study uncovers that if the nozzle placed near the cutting zone, optimum MQL spray achieved from low oil and high airflow rate, verified from Phase Doppler Anemometry and Particle image velocimetry.…”
Section: Mql In Millingmentioning
confidence: 99%
“…Iskandar et al, [72] Carbon fiber reinforced plastics (CFRP) Dry, MQL, Flood MQL shows 30% less wear at the flank face than pressurized air condition and 22% less wear than flood and dry conditions. Liao et al, [73] NAK80 mold steel (41 HRc) Dry, Flood, MQL Combining superior heat-resistant, coated carbide tool with MQL gives better tool life than other methods.…”
Section: Mqlmentioning
confidence: 99%